Factors influencing the intention to use the Nigerian central bank digital currency (E‑Naira) among Nigerian retailers - Ahmed, Mahfooz; Al-Hussaini, AbulFathi Ibrahim Saleh; Abubakar, Adamu (Springer Nature, 2025)
This study explores the determinants of e-Naira adoption among Nigerian retailers, using the technology acceptance model (TAM) as its theoretical foundation. As Nigeria’s central bank-issued digital currency gains prominence, understanding what drives retailers to adopt e-Naira is vital for its widespread implementation. The research employed a survey distributed to retailers in Abuja, with data from 326 respondents analysed using partial least squares structural equation modelling (PLSSEM) in SmartPLS 3. The findings indicate that perceived ease of use, perceived usefulness, and trust significantly influence retailers’ intentions to adopt e-Naira, which is consistent with TAM predictions. Conversely, financial concerns were not significant predictors of adoption. Emotionality was identified as a significant mediator between trust, financial concerns, and adoption intentions. These insights provide valuable guidance for policymakers and stakeholders in promoting digital currencies, particularly in emerging markets like Nigeria. The study contributes to the expanding literature on central bank digital currencies, highlighting the factors that influence their adoption among retailers in Nigeria.